Analysis of Match Management the Finals League 3 Central Java Competition 2023 - David Setiawan; Zahrah Zakiya Ahda (Universitas Negeri Semarang, 2025)
The Central Java PSSI Provincial Association has successfully organized the 2023 Central Java League 3 final match well, without any riots between teams or supporters. However, there needs to be a follow-up or evaluation of the competition that has been run so that the quality of management can be improved and developed better for football competitions in the Central Java region. The purpose of this study is to determine the management process of the Central Java PSSI Asprov. This research method uses qualitative descriptive with data collection techniques through interviews and documentation with validity checked through source triangulation. The data obtained were analyzed through the following stages: data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the 2023 Central Java League 3 final match carried out a management strategy with 4 processes, namely planning, organizing, implementing, and supervising. The planning process, by conducting a manager meeting and match coordination meeting. The organizing process is divided into 2, namely the steering committee and the organizing committee. Implementation process, the steering committee checks the infrastructure before the match and supervises the progress of the match, while the organizing committee carries out their respective duties during the match. The supervision process is carried out by the steering committee assisted by security and police. The conclusion of this study is that the management strategy in the final match of the 2023 Central Java League 3 competition applies the management process theory of Dr. Nugroho Susanto which includes 4 processes, namely planning, organizing, actuating, and controlling.